INTERDISCIPLINARY TREATMENT IN AN ADULT PATIENT WITH CLASS III SKELETAL MALOCCLSION-CASE REPORT - Pop Silvia-Izabella; Rus Krisztina; Pop Radu-Vasile; Pop Oana; Contac Laura-Roxana; Ileana Mitre; Bran Simion (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study: The aim of this paper is to report a successful interdisciplinary approach on an adult patient with a skeletal and dental anomaly. The secondary objective was to illustrate the importance of the treatment planning using visualized treatment objectives. Materials and methods: The present case report describes the multidisciplinary approach on an adult patient with a class III malocclusion with crowding, hyper-divergent pattern, mandibular prognathism, anterior and bilateral crossbite and maxillary hypoplasia. Results: The treatment included fixed orthodontic appliance and 2 phase orthognathic surgery. Conclusions: Esthetics and function were significantly improved. The class III skeletal malocclusion treatment frequently requires an interdisciplinary approach such as surgical, orthodontic and prosthetic-restorative collaboration.